Motivations to attend a non-traditional conference: Are there differences based on attendee demographics and employment characteristics?. Issue 4 (20th October 2018) - Draper, Jason; Neal, J. A.
Abstract: This study assessed the motivations of attendees of a very different type of conference than have been addressed in other studies (e.g., educational). Delegates of the Conference for Food Protection Biennial Meeting were sent an online survey to complete regarding their motivations to attend the debate style meeting, which was created to identify and address emerging food safety issues and develop recommendations for stakeholders. The motivation scale was modified from an existing study. Results revealed delegates' preferences were to focus on the purpose of the meeting, rather than the destination, networking, and other motivations typically identified in prior studies. For example, less-educated delegates have a higher level of motivation for professional development, which is not currently part of the conference, than higher educated (e.g., PhD/Professional). Results offer opportunities for development of such a conference, such as adding more educational sessions for less-educated delegates.